When the world smells of coffee / Ahmad Lutfi Anis - Anis, Ahmad Lutfi (UiTM Press, 2024)
Damai is a young man pursuing his dream of obtaining a doctorate degree at a public university. He maintains a close relationship with his grandfather, whom he greatly admires and constantly seeks motivation, wisdom, and advice. His supervisor, Dr. Rajesh is an Indian expatriate, a unique character who Damai found to be out of the ordinary, witty, and possesses his own brand of philosophy to life.